Effect of individuals' local persistence, and spatial and temporal scale, on density-dependent growth: a study in brown trout Salmo trutta. Issue 3 (2nd July 2016) - Závorka, L.; Horký, P.; Höjesjö, J.; Slavík, O.
Abstract : This study focuses on the mechanism of density-dependent growth in a stream-dwelling landlocked population of brown trout Salmo trutta. Specifically, body growth estimated by scale reading was examined in relation to population density and recapture rate (approximation of persistence of individuals within a location associated with dispersal and mortality) across 7 years and two spatial scales – a reach and a whole stream. In concordance with previous studies, the whole-stream population density had a crucial effect on body growth in juveniles, but not in adult individuals. Furthermore, growth was negatively associated with the whole-stream population density in reaches with a low recapture rate, whereas no such relationship could be detected in reaches with a high recapture rate. Since persistence within a certain locality increases the familiarity of individuals with the habitat and with other conspecifics, we suggest that the negative effect of population density on growth might be relaxed in groups with a high recapture rate by positive influence of the familiarity both within the habitat but also towards other conspecifics, which decreases competition pressure.